Identificação e caracterização de Staphylococcus aureus isolados de fossa nasal e glândula mamária de vacas leiteiras por diferentes métodos - Renata de Paoli Santos (2017)
Staphylococcus aureus is regarded as one of the most important pathogens in bovine mastitis due to the difficulty of its control in dairy herds associated mainly with the low response to antimicrobial therapy and the various virulence factors. It should be noted that S. aureus represents an important public health problem, mainly related to methicillin-resistant S. aureus (MRSA) of animal origin. The cow's udder is the most important source of S. aureus. However, this pathogen may be isolated from several extra mammary sites (i.e. nasal cavities and skin) in the animal, and these sites are likely to be important sources, often not adequately considered in the epidemiology of intramammary infections by this pathogen. In this context, the objective of the present study was characterize S. aureus isolates from mammary gland and extra mammary site (nasal carriages). For this purpose, 379 bacterial samples from cases of subclinical mastitis and nasal swab from two commercial farms were used in the municipalities of Quartel Geral (Herd 1) and Juiz de Fora (Herd 2) both located in Minas Gerais State, Brazil. From those bacteria samples, for spa typing, we selected 116 S. aureus strains from of persistent and transient intramammary infections and nasal swab. The identification of S. aureus isolates was performed as recommended by the National Mastitis Council, which were later confirmed by automated methods (such as MALDI-TOF) and molecular biology (such as 16 srRNA, aur-nuc and spa-typing). The minimum inhibitory concentration (MIC) to antimicrobials commonly used in veterinary medicine used was determined by the VITEK® 2 device. In addition, the phenotypic profile of methicillin resistant S. aureus (MRSA) was determined by agar diffusion test using discs of oxaciclin and cephaloxitin, besides the automated VITEK® 2 automated apparatus, and confirmed by detection of mecA genes by PCR. Here, we found four spa types, t605, t198, t127 and t089 representing 94.68% (89/94), 1.06% (1/94), 1.06% (1/94), 3.19% (3/94), respectively. The first two spa-typing become from milk samples and the last two spa-typing are from nasal carriages. For antimicrobial susceptibility and MIC analyzes, the results were the high occurrence of multiresistance and absence of methicillin resistance detected by the genes for mecA gene. Also in the study, no relationship between the S. aureus nasal carriage and the the intramammary infections in dairy cattle was found. Furthermore, the S. aureus isolates from transient and persistent intramammary infections did not differ by spa-typing, suggesting that the persistence of infection was mainly determined by cow factors. To the best of our knowledge, this is the first study carried out in Brazil that determine the resistance profile and the spa-typing method performed in S. aureus isolates from cases of persistent and transient mastitis and extra mammary niche (nasal swab).